Ladies of the lake [large type] - Gohlke, Cathy (Thorndike Press large print Christian romance series., 2023)
"When she is forced to leave her beloved Prince Edward Island to attend Lakeside Ladies Academy after the death of her parents, the last thing Adelaide Rose MacNeill expects to find is three kindred spirits. The "Ladies of the Lake," as the four girls call themselves, quickly bond like sisters, vowing that wherever life takes them, they will always be there for each other. But that is before: Before love and jealousy come between Adelaide and Dorothy, the closest of the friends. Before the dawn of World War I upends their world and casts baseless suspicion onto the German American man they both love. Before a terrible explosion in Halifax Harbor rips the sisterhood irrevocably apart. Seventeen years later, Rosaline Murray receives an unsuspecting telephone call from Dorothy, now headmistress of Lakeside, inviting her to attend the graduation of a new generation of girls, including Rosaline's beloved daughter. With that call, Rosaline is drawn into a past she'd determined to put behind her. To memories of a man she once loved . . . of a sisterhood she abandoned . . . and of the day she stopped being Adelaide MacNeill" --